From garbage to product and service systems: A longitudinal Finnish case study of waste management evolution - Peura, Pekka; Voutilainen, Olli; Kantola, Jussi (Elsevier Ltd., 2022)
This longitudinal case study analyses the development of the pioneering waste management (WM) system in the Vaasa region of Western Finland, since the late 1980s to the present. It reflects the general features of the evolving WM from the one-bag system and throwaway culture towards today’s circular economy and product service systems. The Vaasa region is an excellent example of how WM has evolved in Finland, which also follows the main direction of travel in Europe. The main features have been: (1) closing of dumping sites, minimizing dumping of waste and concentrating dumping to well-organized and environmentally managed sites; (2) development of comprehensive source separation systems for reuse of materials and energy; (3) building of waste treatment systems, consisting of different technical solutions connected with reuse and energy generation solutions. This evolution has resulted in expanding regional collaboration, where large investments are integrated within larger areas and consortia. The share of reused materials has grown significantly and dumping has decreased to close to zero. The practices of the circular economy are emerging and partly established. In this evolution, praxis does not immediately follow after “a brilliant idea”, but only after the societal structuring process, including paradigmatic changes in attitudes, social norms, policies and regulation, customer behaviour, economic structures, and separate and systemic technological solutions and value chains. This research can add value both in terms of knowledge and science, and in being a change agents more practically. In the future, a strategic shift from WM to material management, and from public service to feasible businesses will be the next steps.
Keywords: waste management; reuse of waste; circular economy; product service systems